Бюджетні видатки на соціальний захист населення в Україні - Насібова, Ольга Вікторівна (Одеський національний університет імені І. І. Мечникова, 2015)
The modern state of budgetary charges of the system of social defense of population is considered in the conditions of transformation transformations. The estimation of charges of the erected budget of Ukraine is carried out after functional classification. Certain structure and basic directions of the budgetary providing of social defense of population.
Budgetary Charges on Social Defence of Population In Ukraine
Keywords: бюджетні видатки; соціальний захист населення; Україна; соціальне забезпечення; бюджетне забезпечення; соціальні послуги; соціальні видатки; соціальні гарантії; social defense of population; budgetary providing; social charges; social services; social guarantees